1981
DOI: 10.1111/j.1365-2028.1981.tb01061.x
|View full text |Cite
|
Sign up to set email alerts
|

Population estimates, densities and biomass of large herbivores in Simanjiro Plains, Northern Tanzania

Abstract: Summary A total of twenty‐four aerial censuses were carried out in the Simanjiro Plains, northern Tanzania, from 1970 to 1972 in order to estimate the populations, densities and biomass of eleven common large herbivores. Results show that amongst wild herbivores zebra and wildebeest have the highest populations which reach a peak during the wet season between March and May. They were estimated to be about 6000 and 5000, respectively. The corresponding densities were 10.96/km2 and 7.44/km2, respectively. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 16 publications
2
34
1
Order By: Relevance
“…They are also found west and south to Mkomazi, Amboseli and sporadically appearing in Serengeti National Park [2], and are probably extinct in Uganda, Sudan and Eritrea [1]. They inhabit scrubland, Acacia woodlands and semi-arid grasslands [5], and are mostly common in areas with an annual rainfall of 40 to 80 cm [16 to 31 inches]. Predictions [4] indicated that in the near future, the species is likely to be confined in protected areas as a result of pressure associated with habitat loss and illegal poaching outside these areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also found west and south to Mkomazi, Amboseli and sporadically appearing in Serengeti National Park [2], and are probably extinct in Uganda, Sudan and Eritrea [1]. They inhabit scrubland, Acacia woodlands and semi-arid grasslands [5], and are mostly common in areas with an annual rainfall of 40 to 80 cm [16 to 31 inches]. Predictions [4] indicated that in the near future, the species is likely to be confined in protected areas as a result of pressure associated with habitat loss and illegal poaching outside these areas.…”
Section: Introductionmentioning
confidence: 99%
“…Their habitats are mostly semi-arid Acacia-Commiphora thornbush, and tend to avoid open areas and those with long grass [1] [2] [3], although they have been at about 1740 m near Mt. Kilimanjaro in Tanzania [1] [5]. It's a water independent species and primarily selective browsers, and forages on leaves and young shoots of shrubs, herbs and trees [1], and in a study in Tsavo East National Park, Kenya, [3] observed that they fed on 150 different plant species.…”
Section: Introductionmentioning
confidence: 99%
“…In common with all sampling methods, once a critical sample size is reached, gains in precision are minimal and further sampling is of no great benefit unless the survey has aims additional to a population estimate. For example, while a sampling intensity of 25 per cent may be appropriate for an area of 570 km2 (Kahurananga, 1981) it is doubtful whether it can be justified for an area of 45 000 km2 (Fuller, 1950). With regard to kangaroo surveys, Caughley (1979b) discusses the role of size of the survey zone in determining sampling intensity.…”
Section: Samplingmentioning
confidence: 99%
“…Buechner et al, 1951;Bowman, 1955;Gilbert and Grieb, 1957;Darling, 1960;Lamprey, 1964;Watson and Turner, 1965;Lovaas et al, 1966;Buss and Savidge, 1966;Field, 1971;Eltringham, 1977;Edroma, 1981; and sample censuses (e.g. Fuller, 1950;Petrides, 1953;Banfield et al, 1955;Schultz and Muncy, 1957;Bergerud, 1963;Watson et ai., 1967;Kahurananga, 1981). Even where blocks are searched transects are usually the method utilized within each unit (e.g.…”
Section: The Counting Unitmentioning
confidence: 99%
See 1 more Smart Citation